New radiocarbon models for the Iron Age in Israel - Finkelstein, Israel; Piasetzky, Eli (Semitica et Classica, 2023)
Abstract New radiocarbon dates for Megiddo and the publication of the full set of dates for Tel Rehov enable us to present an updated model for each of the two sites and a model that combines the two sites and thus achieve robust dates for the phases of the Iron Age I-IIA in the northern valleys. We then update our model for the Shephelah with new results for Khirbet Qeiyafa, Khirbet er-Rei and Lachish published by Garfinkel et al. and present an equally robust model for the south. Finally, we cautiously compare the models for the north and south. Abstract Grâce à de nouvelles datations au radiocarbone pour Megiddo et la publication de l’ensemble des datations pour Tel Rehov nous sommes en mesure de présenter un modèle mis à jour pour chacun des deux sites et un modèle qui combine les deux sites, ce qui permet d’obtenir des datations solides pour les phases de l’âge du Fer I-IIA dans les vallées septentrionales. Nous mettons ensuite à jour notre modèle pour la Shephelah avec les nouveaux résultats pour Khirbet Qeiyafa, Khirbet er-Rei et Lachish publiés par Garfinkel et al. et présentons un modèle tout aussi solide pour le Sud. Enfin, nous comparons, avec prudence, les modèles pour le Nord et pour le Sud.